Self-Collected Nasal Swabs for Respiratory Virus Surveillance. (17th October 2015) - Jackson, Michael L.; Nguyen, Matthew; Kirlin, Beth; Madziwa, Lawrence
Abstract: We tested whether 135 patients reporting acute respiratory illness (ARI) could self-collect nasal swab specimens and ship them for laboratory testing. Most subjects (78.2%) collected and shipped their specimens without errors; 10.5% excluded ≥1 packing components; 12.9% made ≥1 packing errors. Self-swabbing at home is feasible for confirming ARI etiology.